Opening new gateways to workflows for life scientists. - Karasavvas, K; Wolstencroft, K; Mina, E; Cruickshank, D; Williams, A; De Roure, D; Goble, C; Roos, M (2012)
The combination of highly complex biology problems and varying IT skills among life scientists poses a unique challenge in designing bioinformatics programs. The set of tools and initiatives described in this work shows new ways of making life science workflows more accessible to the community. Our aim is to help bioinformaticians help biologists. We present how to make Taverna workflows available from within Galaxy, both widely used bioinformatics platforms. Calling Galaxy tools from Taverna is also discussed. In addition, we describe a web application that allows a user to run arbitrary Taverna workflows by only using a web browser.